The Expression of Religious Positivity in Karen Armstrong’s Sīrah Work - Fiaz, Fozia; Munir, Mohsina (Journal of Islamic and Religious Studies, 2018)
Orientalists contributed much regarding their study of the Holy Qur’ān, Hadith and Sīrah since eighteenth century. Few of them attracted Muslim scholars due to the quality of their work about Islam, like the translation of the Holy Qur’ān, the indexes of Hadith literature and the translations of Arabic Sīrah books in English. These orientalists have left a positive impression regarding their contributions in introducing Islamic literature in West in their native languages. This research paper aims to present the expression of religious positivity in modern orientalist Karen Armstrong’s Sīrah work. This selection is based on the status of this Sīrah writer in present time. Her books are best sellers written on comparative religion and a huge number of people study her books and appreciate her for expressing the positive image of Islam in West. In this study, it will be found out that in which style and angle she has presented her works regarding religious positivity especially the presentation of the personality of the Holy Prophet (peace be on him) to the non-Muslims and non-religious societies.